Bioaccessible phenolics and flavonoids from wheat flour products subjected to different processing variables. Issue 6 (26th September 2019) - Oghbaei, Morteza; Prakash, Jamuna
Abstract: Background and objective: The study explored the content and in vitro availability of phenolics and flavonoids from wheat flour products fortified with minerals and/or wheat bran (WB) subjected to simulated digestion. The products were flat unleavened breads (roasted or deep fried) prepared with either whole (WWF) or refined wheat flour (RWF). Experimental products had added WB (10% or 20%) and/or minerals (Zn or Fe) at two different levels (10 or 20 mg/100 g with or without 10% WB). A total of eleven products were prepared with each WWF and RWF including a control with no fortification. Findings: Results indicated that addition of WB increased the total and bioaccessible phenolics and flavonoids in all products, while mineral fortification had an opposite effect. Addition of WB along with minerals improved the content and bioaccessibility to some extent. Products prepared with RWF had a lower content and accessibility of phenolics and flavonoids in comparison with WWF products. In processing methods, deep frying had a negative influence on both amount and availability of bioactive constituents. Conclusions: Study indicates that WB can be used for enriching wheat flour and can also be used as co‐fortificant with minerals. Nutritionally roasting is a better method for making flat breads than deep frying. Significance and novelty: Nutritionally bran and mineral fortification are desirable, specifically for products prepared with refined flour. Addition of bran increases the fiber content and hence the bioactive components associated with fiber. It was interesting to investigate the bioaccessibility of bioactive components from such products as there were multiple processing variables involved, namely, compositional alteration of food matrix on addition of bran and minerals, different processing treatments used, and use of whole and refined flours. To our knowledge, such a study has not been reported earlier.